De berørte etter 22. juli Forskningsetiske perspektiver - Dyb, Grete (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2016)
Research following the terrorist attacks July 22nd 2011 has been especially challenging, due to the extreme nature of the events and the trauma for those involved; both directly as victims and indirectly as family, relatives and friends.